Etica e impresa: come e perché 'ritornare' a Polanyi - La Rosa, Michele (Business and Ethic: why should we go back to Polanyi?, 2008)
The essay, after trying to do a synthesis of today's debate about business and ethics, proposes to return to Karl Polanyi starting from a different meaning of the three founding principles proposed by the author (exchange, reciprocity and redistribution).
Sociology
Keywords: business ethics; business people; essay (literary form); professional ethics